Surgical outcomes in aspirin‐exacerbated respiratory disease without aspirin desensitization. Issue 10 (18th June 2020) - Grose, Elysia; Lee, Daniel J.; Yip, Jonathan; Cottrell, Justin; Sykes, Jenna; Lee, Jason K.; Lee, John M.
Abstract : Background: Aspirin‐exacerbated respiratory disease (AERD) represents a severe endotype of chronic rhinosinusitis with nasal polyposis. Although aspirin desensitization (AD) has emerged as an effective therapeutic option, the natural history of AERD without AD remains unclear. Methods: A retrospective review was conducted of AERD patients who underwent endoscopic sinus surgery (ESS) without AD between 2010 and 2019. The primary outcomes were revision surgery rate and time to revision surgery. Secondary outcomes included changes in 22‐item Sino‐Nasal Outcome Test (SNOT‐22) scores and Lund‐Kennedy endoscopy scores (LKES). A subgroup analysis was performed for patients on monoclonal antibody therapy (MAT). Results: Of 141 patients, 37 (26.2%) underwent revision ESS with a median time to revision of 3.3 (interquartile range [IQR], 2.2‐4.9) years. The probability of remaining free of revision surgery at 1, 3, and 5 years was: 98.2% (95% confidence interval [CI], 95.7‐100.0%), 78.8% (95% CI, 70.2‐88.4%), and 44.8% (95% CI, 32.4‐62.1%), respectively. SNOT‐22 scores decreased by 34 (IQR, 18‐52) points at 6 months and 27 (IQR, 20‐46) points at 1 year postoperatively. In the revision cohort, the decrease in SNOT‐22 score was not sustained at 1 year postoperatively. No difference was found in time to revision compared with those without MAT ( p = 0.23). Conclusion: A significant proportion of AERD patients benefit from ESS and medical therapy alone without AD. This study presents preliminary results on the impact of MAT on surgical outcomes as it is limited by the small sample size. Further research on the use of MAT in AERD is needed.